The relationship between environmental literacy, ecological footprint awareness, and environmental behavior in adults - Mehmet Salih Yildirim; Ayşe Elkoca; Gönül Gökçay; Dursun Alper Yilmaz; Metin Yıldız (BMC Public Health)
Abstract Background Environmental literacy and ecological footprint awareness encouraging them to consume less energy, reduce waste and use natural resources more sustainably. Aim In this study, the aim was to determine and compare the relationship between environmental literacy, ecological footprint awareness, and environmental behaviors of adults. Methods The research was conducted in a descriptive and cross-sectional type. The universe of the research was individuals aged 18 and over in a province located in the west of Turkey (n: 398) between April 2022 and January 2023. Data were analyzed using SPSS 22.0, G*Power 3.1, and R programming language 4.1.3 programs. Results This study revealed that environmental literacy and ecological footprint awareness significantly affected environmental behaviors (p < 0.05). In the study, the ecological footprint awareness variable has a partial mediating effect on the environmental behaviors variable (LLCI = 0.1226, ULCI = 0.2559). Conclusions Increased environmental literacy and ecological footprint awareness positively affect environmental behaviors. Future studies should explore these relationships in diverse populations. Longitudinal studies on attitudes towards environmental behaviors are recommended.